2022
DOI: 10.1080/21655979.2022.2063649
|View full text |Cite
|
Sign up to set email alerts
|

Propofol modulates glycolysis reprogramming of ovarian tumor via restraining circular RNA-zinc finger RNA-binding protein/microRNA-212-5p/superoxide dismutase 2 axis

Abstract: Metabolic reprogramming refers to the transformation of the whole metabolic network covering glycolysis and mitochondrial metabolism, which is primarily manifested as the Warburg effect and mitochondrial metabolic reprogramming. Propofol (Pro) has been testified to suppress the malignancy of diversified human cancers. Nevertheless, its role in glycolysis is still uncertain. The purpose of this study was to determine whether Pro modulated glycolysis in ovarian cancer (OC) cells. Cell proliferation, apoptosis, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…According to previous reports, ZNF family members play a regulatory role in tumorigenesis. For example, ZNF212 and ZNF367 can regulate the apoptosis of ovarian tumour cells and the proliferation of colorectal cancer cells, respectively [ 31 , 32 ]. In the ZNF protein family, ZNF 471, ZNF1 and ZNF20 are involved in tumour progression through various pathways, including prognostic features, immune infiltration, TME, and tumour-related signalling pathways [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, ZNF family members play a regulatory role in tumorigenesis. For example, ZNF212 and ZNF367 can regulate the apoptosis of ovarian tumour cells and the proliferation of colorectal cancer cells, respectively [ 31 , 32 ]. In the ZNF protein family, ZNF 471, ZNF1 and ZNF20 are involved in tumour progression through various pathways, including prognostic features, immune infiltration, TME, and tumour-related signalling pathways [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A valuable study that shows the importance of circRNAs as new therapeutic targets is that by Qu et al. [ 125 ]. This study used propofol as an inhibitor of malignancy in ovarian tumors.…”
Section: Circrnas Regulate Cancer Metabolic Reprogrammingmentioning
confidence: 99%
“…Recently, Yue et al demonstrated that HIF-1α positively regulated miR-212 expression and resulted in pancreatic ductal adenocarcinoma progression [ 99 ]. Propofol inhibited ovarian cancer cells growth and glycolysis by elevating miR-212-5p expression [ 100 ]. Higher miR-212-5p expression showed a neuroprotective effect in rats with isoflurane-induced cognitive dysfunction by inhibiting neuroinflammation [ 101 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%